PEMBELAJARAN MUSIK BAGI ANAK BERKEBUTUHAN KHUSUS DI SMP NEGERI 4 PAYAKUMBUH - Bobby Ervan; Yuliasma Yuliasma; Tulus Handra Kadir (SENDRATASIK UNP, 2013)
Abstract The aim of this research was to describe the learning process on music subject for students with particular needs (blind) at SMP Negeri 4 Payakumbuh. This was a qualitative research that used descriptive method. This was done by seeing, observing and collecting information related to the research object. The data then was described descriptively. The result of the research that the students with particular needs did not get similar materials, methods, and learning media to the normal students as all of those required visual capability. In addition, there was not any specific teacher paid to help them in learning.   Keyword : musik, anak berkebutuhan khusus, kualitatif, deskriptif.